2020
DOI: 10.1111/ger.12513
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated oral health and frailty index among older Americans

Abstract: Frailty is an important implication of ageing. Frailty is a state characterised by higher vulnerability to adverse health outcomes for older adults. 1 Frailty is prevalent among community-dwelling older adults and the ageing populations. 2 The evidence indicates that frailty is associated with mortality, chronic diseases, depression, dependence and reduced quality of life. 3 The underlying mechanism of frailty is related to impairments to the neuro-immuno-endocrine system, physical activity and nutritional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…Self-rated oral health helps summarize how people evaluate their own oral health ( Locker, Maggirias & Wexler, 2009 ; Locker, Wexler & Jokovic, 2007 ). Older adults are more likely to be confused by complicated and lengthy questions, including discomfort with a complete oral clinical examination; therefore, self-rated oral health can be used as a quick, but effective tool for assessing oral health among the elderly ( Hakeem, Bernabé & Sabbah, 2021 ). Current studies have supported using these single-item measures instead of lengthy indexes in low-resource settings ( Lawal, 2015 ), where there are limited healthcare providers, or when a complete oral examination is infeasible ( Hakeem, Bernabé & Sabbah, 2021 ; Lundbeck, Smith & Thomson, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-rated oral health helps summarize how people evaluate their own oral health ( Locker, Maggirias & Wexler, 2009 ; Locker, Wexler & Jokovic, 2007 ). Older adults are more likely to be confused by complicated and lengthy questions, including discomfort with a complete oral clinical examination; therefore, self-rated oral health can be used as a quick, but effective tool for assessing oral health among the elderly ( Hakeem, Bernabé & Sabbah, 2021 ). Current studies have supported using these single-item measures instead of lengthy indexes in low-resource settings ( Lawal, 2015 ), where there are limited healthcare providers, or when a complete oral examination is infeasible ( Hakeem, Bernabé & Sabbah, 2021 ; Lundbeck, Smith & Thomson, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Self-rated oral health likely differs based on the respondent’s emotional state, physical state, demographic characteristics, economic status, underlying diseases, or health-related behaviors; those who report having poor oral health probably use a somewhat different frames of reference in their self-evaluation than those who report positive oral health, inducing inconsistent findings in research publications ( Locker, Maggirias & Wexler, 2009 ; Locker, Wexler & Jokovic, 2007 ). Despite these inconsistencies, previous studies have suggested that self-rated rating is commonly used to predict both current and future health factors among the elderly ( Balasubramanian et al, 2021 ; Hakeem, Bernabé & Sabbah, 2021 ; Lundbeck, Smith & Thomson, 2020 ). Therefore, it is important to consider the different frames of reference among study participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of maintaining good oral health at older ages and the incorporation of oral health indicators in routine geriatric assessments has been discussed in the literature 18 . Thus, a comprehensive assessment of the oral health of these individuals is urgent, focusing on the comprehensive care of this population, which has peculiar characteristics regarding the presentation, installation and outcome of diseases and health problems, translated by greater vulnerability to adverse events 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A importância da manutenção de uma boa saúde bucal em idades mais avançadas e a incorporação de indicadores de saúde bucal nas avaliações geriátricas de rotina vem sendo discutida na literatura 18 . Dessa forma, é premente uma avaliação da saúde bucal desses indivíduos de forma abrangente, com foco no cuidado integral dessa população, que possui características peculiares quanto à apresentação, instalação e desfecho de doenças e agravos em saúde, traduzidas pela maior vulnerabilidade a eventos adversos 19 .…”
Section: Introductionunclassified